Formulasi Sediaan Losio Minyak Biji Mengkudu (Morinda citrifolia L.) Sebagai Repellent Nyamuk - Maria ulfa; Achmad Himawan; Sri Astuti Kalni (Jurnal Farmasi dan Ilmu Pengobatan, 2019)
Noni seeds (Morinda citrifolia L) have an odor that is not liked by mosquitoes and contain alkaloid compounds and cardiac glycosides which act as mosquito repellents which have the ability to protect humans from disturbances or mosquito bites. This study aims to obtain a physically stable anti-mosquito lotion formula from noni seed oil which conducted by steam distillation method. Noni seed oil formulated into lotion preparations with variations in oil concentration (2%, 4% and 6%). Physical stability of the lotion then tested based on organoleptic observation, homogeneity test, pH test, emulsion type test, viscosity test, dispersion test, adhesion test, flow test and test on conditions before and after accelerated storage. The results indicate that all preparations with varying concentrations of oil are stable and effective as mosquito repellents. The noni seed oil lotion produced met the physical quality requirements of lotion preparations and effective as mosquito repellent on concentration 6% of noni seed oil. Keywords: Noni seed oil, lotion, physical stability, repellent